A Single Case Study On Pratishyaya (Acute Rhinitis) Treated With Shaman Aushadhi - Nematullah, Md; Das, Madhumita; Mahmood, Sufia; Mahapatra, P B Kar (International Research Journal of Ayurveda & Yoga, 2021)
In Ayurveda Pratishyaya is described under Nasa Roga. Which is characterised by Shira sula(headache) ,Nasa srava (rhinorrhoea), Jwara (fever), Angamarda (bodyache), Kshawathu (sneezing), Kasa(cough), Aruchi(Anorexia). Pratishyaya may be correlated with Rhinitis in modern medicine where nasal mucous membrane inflamed due to different infection of allergens. In present era, the era of industrialisation and modernization there are some disease which need to be given attention, Pratishyaya is one of them. As respiratory system is continuous contact with the external environment since birth considered as prime site of hypersensitization. Improper management or negligence can lead to lots of complications like Badhirya (deafness), Andhatva (blindness), Gandhanasa (anosmia) etc. In this case patient of acute rhinitis has been treated with Ayurvedic classical drugs Triphala guggula and Laxmivilas rasa. After two weeks the features of pratisyaya ( acute rhinitis) has been reduced markly and patient relieved significantly.